2022
DOI: 10.1021/acs.jpclett.2c01180
|View full text |Cite
|
Sign up to set email alerts
|

Entropy-Driven Stabilization of Multielement Halide Double-Perovskite Alloys

Abstract: Currently, a major obstacle restricting the commercial application of halide perovskites is their low thermodynamic stability. Herein, inspired by the high-stability high-entropy alloys, we theoretically investigated a variety of multielement double-perovskite alloys. First-principles calculations show that the entropy contribution to Gibbs free energy, which offsets the positive enthalpy contribution by up to 35 meV/f.u., can significantly enhance the material stability of double-perovskite alloys. We found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 68 publications
1
13
0
Order By: Relevance
“…Previous work found ES in (Cs,FA)PbI 3 , 297 (FA,GA)PbBr 3 , 298 (Cs,FA,MA)PbI 3 , 299 (Cs,FA,MA)Pb(Br,I) 3 , 221,300 and (Cs,FA,MA,Rb)-PbI 3 , 220,222 and ES was also recently demonstrated in double HP 28,301 and ''hollow'' HP. 302 Long anneals of CH 3 NH 3 PbI 3 were argued to maximize configurational entropy of the organic cation, which was found to stabilize the cubic polytype and improve Table 2 Inorganic HP compositions with the greatest ES term at 300 K whose lattice parameters are known and end-members are all experimentally observed with mixing on all sublattices.…”
Section: Organic A-site Components (Hybrid Organic-inorganic Hp)mentioning
confidence: 78%
See 1 more Smart Citation
“…Previous work found ES in (Cs,FA)PbI 3 , 297 (FA,GA)PbBr 3 , 298 (Cs,FA,MA)PbI 3 , 299 (Cs,FA,MA)Pb(Br,I) 3 , 221,300 and (Cs,FA,MA,Rb)-PbI 3 , 220,222 and ES was also recently demonstrated in double HP 28,301 and ''hollow'' HP. 302 Long anneals of CH 3 NH 3 PbI 3 were argued to maximize configurational entropy of the organic cation, which was found to stabilize the cubic polytype and improve Table 2 Inorganic HP compositions with the greatest ES term at 300 K whose lattice parameters are known and end-members are all experimentally observed with mixing on all sublattices.…”
Section: Organic A-site Components (Hybrid Organic-inorganic Hp)mentioning
confidence: 78%
“…Moreover, weak bonding allows entropy to dominate HP Gibbs energies. 28 A given alloy composition change can be net stabilizing if that change's configurational ES outweighs any enthalpic destabilization. In order to screen for promising alloy compositions, we assume each sublattice (A cation, B cation, and X anion) behaves like an ideal solid solution 12 to calculate the entropy of mixing (configurational entropy; S/R), as well as the ES term in the Gibbs energy equation at 300 K:…”
Section: Introductionmentioning
confidence: 99%
“…40 As notable examples for the entropy stability effect in halide perovskites, Yi et al claimed that adding Cs into FAPbI 3 (FA stands for formamidinium) can suppress the formation of the undesired δ phase, 32 Gao et al found perfect agreement between the theoretical prediction and experiment for stable FA 1−x Cs x SnI 3 alloy, 27 and Wang et al found the entropy effect significant in stabilizing doubleperovskite alloys. 40 Nevertheless, the evaluation of mixing entropy in these works was based on the ideal solution model; i.e., all systems (configurations) equally contribute to the thermodynamic properties of the canonical ensemble. The free energy of alloy formation was then calculated by superimposing the mixing entropy term over the calculated (usually the minimal) alloy formation energy.…”
Section: Introductionmentioning
confidence: 99%
“…The idea of entropy-driven stability from high entropy alloys , has been adapted for nonmetallic systems such as oxides , and perovskites . As notable examples for the entropy stability effect in halide perovskites, Yi et al claimed that adding Cs into FAPbI 3 (FA stands for formamidinium) can suppress the formation of the undesired δ phase, Gao et al found perfect agreement between the theoretical prediction and experiment for stable FA 1– x Cs x SnI 3 alloy, and Wang et al found the entropy effect significant in stabilizing double-perovskite alloys . Nevertheless, the evaluation of mixing entropy in these works was based on the ideal solution model; i.e., all systems (configurations) equally contribute to the thermodynamic properties of the canonical ensemble.…”
Section: Introductionmentioning
confidence: 99%
“…Following the well-established strategies developed for conventional semiconductors, alloying has been proposed as a promising approach to tune and improve the optoelectronic properties of several silver–bismuth halides and other double perovskites. The partial replacement of Ag + and Bi 3+ cations by other isovalent cationssuch as Cu + , Na + , In 3+ , and Sb 3+ has proved effective in engineering bandgaps and tuning internal strains for this family of semiconductors. ,, In 2020, Li et al successfully replaced Bi 3+ with Sb 3+ cations in the Cs 2 AgBiBr 6 double perovskite, yielding a bandgap lowering by up to 170 meV for improved solar spectral matching . Interestingly, the authors reported a bandgap bowing (i.e., narrower bandgap for intermediate alloy compositions) and ascribed it to the formation of type II band alignment between Sb and Bi sites.…”
mentioning
confidence: 99%